1996
DOI: 10.1002/(sici)1096-9071(199607)49:3<178::aid-jmv4>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotypes of hepatitis C virus in Nigeria

Abstract: A pilot survey of hepatitis C virus (HCV) infection in Nigeria was carried out on healthy adult blood donors and children of preschool age. Sixteen of 200 (8%) donors were positive for antibodies using a second generation enzyme-linked immunosorbent assay (ELISA) but all of the children were negative. Supplementary testing of the ELISA-positives using a recombinant immunoblot assay (RIBA-2) confirmed the presence of antibody in four and two others were indeterminate. Four of the anti-HCV-positive sera and one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
16
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 15 publications
5
16
0
Order By: Relevance
“…A low prevalence of HCV also has been reported among other populations in sub-Saharan Africa (Nigeria, 2% 3 and South Africa, 1.2% 12 ), but higher estimates have been reported in Zaire (6%), 13 Cameroon (6%), 2 and Mozambique (3.2%).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…A low prevalence of HCV also has been reported among other populations in sub-Saharan Africa (Nigeria, 2% 3 and South Africa, 1.2% 12 ), but higher estimates have been reported in Zaire (6%), 13 Cameroon (6%), 2 and Mozambique (3.2%).…”
Section: Discussionmentioning
confidence: 85%
“…We also found a higher rate of discordance between the EIA-3 and RIBA-3 results than previously reported. 3,14 The low specificity and high levels of false-reactive results with the HCV EIA-3 among populations in tropical areas remain an important issue and might result from cross-reactivity with tropical pathogens or the presence of interfering substances that bind to the solid phase. The available HCV screening tests may be not suitable for routine serologic diagnosis of hepatitis C in African populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is perhaps surprising that studies conducted in countries west of Cameroon have not revealed the presence of genotype 4 (Jeannel et al, 1998). Only one study, concerning Nigeria, the closest West African neighbour of Cameroon, has documented the presence of this genotype (Oni & Harrison, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Within the genotypes, diversity between isolates can be considerable. This is clearly seen, for example, in genotypes 3 and 4 where up to nine subtypes have so far been identified in each genotype (Bukh, 1995 ;Fretz et al, 1995 ;Mellor et al, 1995 ;Simmonds, 1995 ;Oni & Harrison, 1996). Complete nucleotide sequences have been determined for at least 26 HCV genomes representing genotypes 1a, 1b, 1c, 2a, 2b, 2c, 3a and 3b and the putative genotypes 10a and 11a.…”
Section: Introductionmentioning
confidence: 98%